Effects of training frequency on physical fitness in male prepubertal tennis players - Sanchis-Moysi, J.; Dorado, C.; Arteaga-Ortiz, R.; Serrano-Sanchez, J. A.; Calbet, J. A. L. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Aim of the present study was to test if training frequency determines physical fitness and fat mass accumulation in prepubertal male tennis players (TP). METHODS: Body composition scans (DXA), jump performance (SJ and CMJ) and 30 m running speed tests were conducted in 24 TP (10.6 years) and 17 physically active boys. Tennis players were divided into two groups (TP5: playing 5 d/week, n.=14; TP2: playing 2 d/week, n.=10). RESULTS: Compared to TP5 and TP2, controls had more total body fat (+23-28%) and fat mass in the trunk (+42-43%) and legs (+13-19%), respectively (P<0.05). The relative VO2max was higher in TP2 (12%) and TP5 (15%) than in controls (P<0.001). A positive correlation was observed between weekly trainng hours and VO2max (r=0.42, P<0.05, N.=24). Compared to controls, TP5 and TP2 jumped higher in SJ and CMJ (P<0.05) and ran faster in the 30 m test (P<0.05). Similar VO2max, jumping heights and running speed times were observed between TP5 and TP2. After adjustment for the percentage of body fat and age, TPs reached higher VO2max values than controls, while differences in SJ, CMJ and 30 m did not reach statistical significance. CONCLUSION: Playing tennis 2 d/week at prepubertal ages was associated to enhanced aerobic power and reduced total and regional adiposity (trunk and legs) compared to non-active boys. Playing 5 d/week only has a small additional effect. TPs had also higher jumping and sprinting performance than the controls, although these differences were accounted for by the increased fat mass of the control boys.